Developing chemically modified redox-responsive proteins as smart therapeutics. Issue 35 (15th April 2019) - Tang, Qiao; Wang, Jianxue; Jiang, Ying; Zhang, Meining; Chang, Jin; Xu, Qiaobing; Mao, Lanqun; Wang, Ming
Abstract : The chemically modified redox-responsive RNase A–NSA could be selectively activated by up-regulated GSH in live cells for targeted cancer therapy. Abstract : The conditional control of protein function in response to the physiological changes of diseased cells is essential to develop smart protein therapeutics. Herein, we report a redox-responsive chemical modification of a protein by conjugating an intracellular glutathione (GSH)-cleavable ligand, NSA, onto a protein residue. We demonstrated that the NSA conjugation of Ribonuclease A (RNase A) enabled the control of the protein function by GSH in an aqueous solution and living cells, with extended applications for targeted cancer therapy using a lipid nanoparticle-based intracellular protein delivery strategy.